Pelatihan Monitoring & Evaluasi Infrastruktur Daerah Dan Pengawasan Tata Ruang di Kawasan Mamminasata Berbasis Sistem Informasi Geografis - Lakatupa, Gafar; Arifin, Mimi; Osman, Wiwik Wahidah; Sastrawati, Isfa; Wahyuni, Sri; Yanti, Suci Anugrah; ., Irwan; Irfan, Muhammad; Pratama, Ichsan Caesar; Gunawan, Muh Albab; Prajana, Muh Reza (Faculty of Engineering UNHAS, 2024)
Mamminasata is a metropolitan urban area in Eastern Indonesia. One of the areas in this metropolitan area is Takalar Regency. An effective and efficient method of monitoring and evaluating infrastructure in Takalar Regency is needed. One method that can be done is by monitoring and evaluating infrastructure in the region based on geographic information systems, which are computer-based information systems used to process and store geographic-based data or information. Monitoring and evaluation is done by looking at the number and distribution of infrastructure spatially. The partner in the implementation of this activity is the Public Works, Spatial Planning, Housing and Settlement Area Office of Takalar Regency. Activities are carried out by providing material and training on the use of Geographic Information Systems in monitoring and evaluating regional infrastructure. Training on monitoring and evaluation of regional infrastructure in the mamminasata region based on geographic information systems aims to increase the capacity of human resources (HR) / civil servants (PNS) in related agencies, especially in the Spatial Planning Division in terms of monitoring and evaluating infrastructure that has been built, as well as more effective and efficient spatial supervision by utilizing Geographic information systems. In conducting monitoring activities, participants were trained to use Arc GIS and Google Earth software. The Google Earth software used is Google Earth software that is run on a smart phone. These two software make monitoring, evaluation, and also supervision easier to do in a large area with limited human resources. From the results of the training, there was a significant increase in the number of participants' knowledge from 16.7% to 100%.